Sunscreen effectivity and physical characterization of avocado oil in nanoemulsion using isopropyl myristate variations - Shabrina, Ayu; Firdausi, Zuhriya Muna; Poerba, Agnes Theresya; Setyani, Diana Anisa; Heroweti, Junvidya (Pharmaciana, 2024)
Unsaturated fatty acids in avocado oil can help reduce erythema brought on by prolonged UV-B exposure. The effectivity of sunscreen absorption into the skin will be enhanced by the use of isopropyl myristate (IPM) in nanoemulsion. The purpose of this study was to determine the physical characteristics and sunscreen effectiveness of avocado oil nanoemulsion (AVN) modified with IPM. 1% (FI), 3% (FII), and 5% (FIII) IPM variation were used to make AVN with 5% oil. The AVN were tested for physical characteristics such as organoleptic, pH, viscosity, rheology, particle size and polydispersity index (PI). The products were also tested for sunscreen effectivity by in vitro and Minimum Erythemal Dose (MED) method. The data obtained were analyzed statistically. The results showed that the AVN was pale yellow and clear with transmittance percentage were 96%. The rheogram showed that the products were newtonian. The pH values range were from 6.62 to 6.66; viscosity 1.65-1.84 dPa.s; particle size < 17 nm, zeta potential was in range of -30,54±1,72 to -37,85±3,11 and PI < 0.5 for all formula. In vitro SPF values were 16.43 ± 4.50 (FI), 16.27 ± 4.20 (FII) and 17.88 ± 3.20 (FIII) (p >0.05), and categorized as ultra protection. MED value were 12.28 ± 1.34 (FI); 12.51 ± 1.68 (FII); and 13.22 ± 1.84 (FIII) (p< 0.05) and categorized as maximum protection. Isopropyl myristate increased the sunscreen product's MED value without changing its physical characteristics.